Isolasi dan Karakterisasi Kitin dari Limbah Cangkang Kerang Asia (Corbicula fluminea): Isolation and Characterization of Chitin from Asian Shell Waste (Corbicula fluminea) - Ameilia Rachmadianty; Fika Aryati; Yurika Sastyarina (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Chitin compounds are compounds that can be found from various animals of the Crustaceae group, for example such as crabs, shrimp, and shellfish. The purpose of this study was to find out the chitin content and chitin characteristics of asian shell waste (Corbicula fluminea). The stage of chitin insulation includes the process of deproteination using Sodium Hydroxide 3.5%, and the next process is the process of demineralization using Hydrochloric Acid 1 N. From the results of the isolation obtained chitin characterization in the form of chitin yield is 82.75%, with a grayish-white powder texture, and odorless, it perfectly soubled in Hydrochloric Acid 1 N, has a water content of 0.1764% and ash content of 58.0753%.